Application of Adobe Premiere-Based Video Learning Media to Progress Understudy Learning Results at SMP Negeri 18 Bulukumba - Muh. Syilfa Nooviar; Nur Fahmi Akhmad; Asri (Ceddi Journal of Education, 2023)
This study aims to improve the learning outcomes of high school students at SMK Negeri 1 Bulukumba through the use of educational videos created with Adobe Premiere Pro. The research methodology employed is classroom action research, conducted in two cycles of data collection through experimentation, observation, and recording, following the steps of Action, Plan, Do, Observe, and Reflect, each consisting of two parts. The collected data were then analyzed using descriptive analysis. Based on the study's findings, it can be concluded that the application of Adobe Premiere Pro-based educational videos significantly enhances students' learning outcomes. In the 1st Cycle, the average learning achievement was 72.8, with 14 students achieving a 56% success rate. In the 2nd Cycle, the average increased to 91.7, with 22 students achieving an 88% success rate, indicating that they passed the minimum competency criteria (KKM) standard for class VII.A/1 students at SMK Negeri 1 Bulukumba. These results demonstrate the effectiveness of integrating multimedia tools in classroom settings to foster better academic performance and engagement among students.